Structural Bases of Atypical Whisker Responses in a Mouse Model of CDKL5 Deficiency Disorder. (1st October 2020) - Pizzo, R.; Lamarca, A.; Sassoè-Pognetto, M.; Giustetto, M.
Abstract: Mutations in the CDKL5 (cyclin-dependent kinase-like 5) gene cause CDKL5 Deficiency Disorder (CDD), a severe neurodevelopmental syndrome where patients exhibit early-onset seizures, intellectual disability, stereotypies, limited or absent speech, autism-like symptoms and sensory impairments. Mounting evidences indicate that disrupted sensory perception and processing represent core signs also in mouse models of CDD; however we have very limited knowledge on their underlying causes. In this study, we investigated how CDKL5 deficiency affects synaptic organization and experience-dependent plasticity in the thalamo-cortical (TC) pathway carrying whisker-related tactile information to the barrel cortex (BC). By using synapse-specific antibodies and confocal microscopy, we found that Cdkl5-KO mice display a lower density of TC synapses in the BC that was paralleled by a reduction of cortico-cortical (CC) connections compared to wild-type mice. These synaptic defects were accompanied by reduced BC activation, as shown by a robust decrease of c-fos immunostaining, and atypical behavioral responses to whisker-mediated tactile stimulation. Notably, a 2-day paradigm of enriched whisker stimulation rescued both number and configuration of excitatory synapses in Cdkl5-KO mice, restored cortical activity and normalized behavioral responses to wild-type mice levels. Our findings disclose a novel and unsuspected role of CDKL5 in controlling the organization and experience-induced modifications of excitatory connections in the BC and indicate how mutations of CDKL5 produce failures in higher-order processing of somatosensory stimuli. This article is part of a Special Issue entitled: Animal Models of Neurodevelopmental Disorders . Graphical abstract: Unlabelled Image Highlights: CDKL5 regulates the organization of synaptic connectivity in the barrel cortex. The barrel cortex of Cdkl5 mutants is less activated. Cdkl5-KO mice show atypical whisker-mediated behavioral responses. Experience-dependent structural plasticity is not prevented by loss of CDKL5. Enhanced sensory stimulation rescues cortical and behavioral defects of Cdkl5-KOs.